2013
DOI: 10.1016/j.freeradbiomed.2013.08.187
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-tocopherol attenuates moderate but not severe colitis and suppresses moderate colitis-promoted colon tumorigenesis in mice

Abstract: Inflammation can promote colon cancer. Mechanistic studies indicate that γ-tocopherol (γT), a major form of vitamin E in diets, has anti-inflammatory and anticancer properties. Here we investigated the effectiveness of γT and a mixture of tocopherols against colitis and colitis-promoted colon tumorigenesis in male BALB/c mice. γT or mixed tocopherols (at 0.1% diet) did not show any effect on colon tumorigenesis induced by azoxymethane (AOM, 10mg/kg) with three cycles of dextran sodium sulfate (DSS at 1.5–2.5%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 44 publications
3
38
0
Order By: Relevance
“…Second, large amounts of unconjugated metabolites, especially 13 ′ -COOH and 13 ′ -OH, which are very low in the plasma, are detected in feces. This observation is consistent with previous reports (12)(13)(14). The high level of carboxychromanols in feces suggests that most long-chain metabolites are not transported to the circulation after being generated in the liver, but rather are excreted via the bile.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Second, large amounts of unconjugated metabolites, especially 13 ′ -COOH and 13 ′ -OH, which are very low in the plasma, are detected in feces. This observation is consistent with previous reports (12)(13)(14). The high level of carboxychromanols in feces suggests that most long-chain metabolites are not transported to the circulation after being generated in the liver, but rather are excreted via the bile.…”
Section: Discussionsupporting
confidence: 93%
“…After a week of acclimatization, mice were randomly divided into control (AIN-93G diet) and ␥ T-or ␦ T-supplemented (0.1% diet) group. These mice were subjected to induction of colon tumorigenesis by azoxymethane/dextran sodium sulfate (AOM/ DSS) as previously described ( 12 ). When the study was terminated, mice were on supplemented diets for more than 150 days ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al [136] reported that the LCMs are unconjugated in feces. Because of the lack of β-glucuronidase treatment, Jiang et al [187] could not distinguish between conjugated and non-conjugated metabolites in their fecal samples, which in turn could support the results from Zhao et al [136] . Wu and Croft [188] concluded that part of the total vitamin E undergoes enterohepatic circulation (estimated to be about 60% in rats) and that the remaining is likely lost via the fecal route [189] .…”
Section: Conjugation Of Metabolitesmentioning
confidence: 93%
“…Feces contain the whole set of vitamin E metabolites, including precursors (TOHs and T3s) and water-soluble SCMs in humans [136] and mice [157,161,187] ; LCMs (especially 13'-COOH) are the main fecal metabolites with > 60% of total metabolites [187] . Zhao et al [136] reported that the LCMs are unconjugated in feces.…”
Section: Conjugation Of Metabolitesmentioning
confidence: 99%